Tinjauan Yuridis Atas Pelaksanaan Pemilu Legislatif Tahun 2014 di Provinsi Kepulauan Riau - Rina Shahriyani Shahrullah; Wagiman Wagiman; Rendra Topan (Journal of Judicial Review, 2017)
Elections , which is a means of implementing the people's sovereignty is exercised directly, free, general, secret, honest, and fair within the unitary State of the Republic of Indonesia based on Pancasila and the Law – the Constitution of the Republic of Indonesia in 1945 and is an important component in the democracies adhere to the system of representation. Implementation of legislative elections by 2014 has been implemented in accordance with laws related legislation. But still found plenty of problems and constraints then then researchers will lift a thesis with the title of the study "Review Of The Implementation Of The Juridical Legislative Elections By 2014 In The Riau Islands Province". And problems examined are the legal basis for the implementation of the legislative elections of 2014, the issues facing the Electoral Commission province of Riau Islands as well as the solution of the Electoral Commission of Riau Islands Province in solving legislative elections by 2014. Research results in the conclusion that the conduct of the legislative elections in the province of Riau Islands has implemented appropriate laws related legislation elections. While the obstacles faced in the Legislative Elections in the province of Riau Islands is verification of political parties, the electoral region, campaign, voters Remain , recapitulation of votes and dispute the results of the general election. To resolve the constraints in the implementation of legislative elections, election commission coordinate with related agencies, election watchdog (Banwaslu) and any solutions that are taken accordance with the provisions of the applicable laws.